Better suited or just more complex? On the fit between user needs and modeller-driven improvements of energy system models. (15th January 2022) - Süsser, Diana; Gaschnig, Hannes; Ceglarz, Andrzej; Stavrakas, Vassilis; Flamos, Alexandros; Lilliestam, Johan
Abstract: Energy system models are advancing rapidly. However, it is not clear whether models are becoming better, in the sense that they address the questions that decision-makers need to be answered to make well-informed decisions. Therefore, we investigate the gap between model improvements relevant from the perspective of modellers compared to what users of model results think models should address. Thus, we ask: What are the differences between energy model improvements as perceived by modellers, and the actual needs of users of model results? To answer this question, we conducted a literature review, 32 interviews, and an online survey. Our results show that user needs and ongoing improvements of energy system models align to a large degree so that future models are indeed likely to be better than current models. We also find mismatches between the needs of modellers and users, especially in the modelling of social, behavioural and political aspects, the trade-off between model complexity and understandability, and the ways that model results should be communicated. Our findings suggest that a better understanding of user needs and closer cooperation between modellers and users is imperative to truly improve models and unlock their full potential to support the transition towards climate neutrality in Europe. Highlights: Modellers refine models, but unclear if that makes models more useful for users. Common need for better representation of environmental impacts and higher transparency. Users seek ways to better represent social and behavioural factors. A better understanding of user needs is imperative to improve energy system models. Co-creative modelling is one possibility to enhance common understanding and impact.